Monocyte subsets in atherosclerosis - Hristov, M.; Heine, G. H. (Hämostaseologie, 2015)
Endothelial dysfunction and chronic inflammation of the arterial wall continuously drive the development of atherosclerotic lesions. Monocytes, as cells of the innate immunity, are particularly involved in this process. In the last decade, heterogeneity of circulating monocytes has widely been acknowledged, and a recent consensus nomenclature subdivides classical, intermediate and nonclassical monocytes. Accumulating experimental and clinical data suggest a differential, subsetspecific contribution of monocytes to the pathology of atherosclerosis.This review summarizes recent key findings on human and mouse monocyte subpopulations, specifically highlighting their phenotype, functional characteristics and mechanisms of recruitment at homeostatic conditions, in atherosclerotic vascular disease, and after acute myocardial infarction.
Keywords: Leukocytes; recruitment; obesity; smoking; coronary artery disease